Synthesis and Pharmacological Evaluation of Some 3-(2-Methylphenyl)-2-Substituted Amino-quinazolin-4(3H)-ones as Analgesic and Anti-inflammatory Agents - Alagarsamy, Veerachamy; Solomon, Viswas Raja; Murugesan, Sankaranarayanan (Arzneimittelforschung, 2008)
A variety of novel 3-(2-methylphenyl)-2-substituted amino-quinazolin-4(3H)-ones were synthesized by reacting the amino group of 2-hydrazino-3-(2-methylphenyl)-quinazolin-4(3H)-one with a variety of aldehydes and ketones. The starting material 2-hydrazino-3-(2-methylphenyl)-quinazolin-4(3H)-one was synthesized from 2-methyl aniline. The title compounds were investigated for analgesic, anti-inflammatory and ulcerogenic index activities. Among these, the compound 2-(l-ethylpropylidene)-hydrazino-3-(2-methylphenyl)-quinazolin-4(3H)-one emerged as the most active compound for analgesic activity, while the compound 2-(1-methylbutylidene)-hydrazi-no-3-(2-methylphenyl)-quinazolin-4(3H)-one showed most potent anti-inflammatory activity of the series and was moderately more potent in its anti-inflammatory activity when compared to the reference standard diclofenac sodium (CAS 15307-86-5). Interestingly, the test compounds showed only mild ulcerogenic potential when compared to acetylsalicylic acid (CAS No: 50-78-2).
Keywords: Analgesics; Anti-inflammatories; Quinazolines, analgesic and anti-inflammatory activities, synthesis